Surface-enabled propulsion and control of colloidal microwheels - T. O. Tasci; P. S. Herson; K. B. Neeves; D. W. M. Marr (Nature Communications, 2016)
Most artificial microdevices include biomimetic features, but existing systems do not yet match living microorganisms in speed and direction control. Here, Tasci et al. use a rotating magnetic field to reversibly assemble colloidal particles into wheels that translate at velocities approaching 100 μm s−1.